Tele-Health Solutions in Practice: A Feasibility Study of Their Advantages, Limitations, and Adoption Potential - Jain, Rohit (Digital Repository of Theses, 2026)
The fast-paced innovation of digital technology was a game-changer in the field of healthcare delivery, and it made “telehealth” a sustainable and significant concept, which contributed to the improvement of the three pillars of Healthcare (HC): accessibility, affordability, and quality. The researcher was interested in finding out the practicality, acceptability, and “telehealth” services by looking at the users' viewpoint, their experiences, and the factors that determine their willingness to try and keep using it. A mixed-method research design was adopted; the first part of the design was the gathering of quantitative data through a Google Forms survey consisting of a fixed number of questions and a convenience sample size of 150 participants; the second part was collecting qualitative data from research study, reports, and journals that had been published before. Among the different methods of statistics for both inferential and descriptive use were frequency analysis, descriptive statistics, chi-square tests, correlation tests, and Mann-Whitney U tests. Content analysis was the technique used for the qualitative part of the data analysis. The results indicated that “telehealth” has not only become a temporary option but also been integrated into the modern HC system. The respondents were extremely satisfied with the convenience, time-saving, and access to services the new system provided. However, other problems like technical constraints, limited physical examinations, and data security still exist. Altogether, these results indicate that “telehealth” can be very promising in improving HC delivery and equity, though stable policies, stable infrastructure, and thorough education of both users and providers are required to make “telehealth” a regularly incorporated part of the global HC systems. Keywords: “Telehealth”, Digital Healthcare, Technology Adoption, Healthcare Accessibility, Feasibility Study, Healthcare Innovation.